Postbiotics derived from recombinant lactic acid bacteria exhibit high IL6-binding capacity and suppress IL6-induced STAT3 signaling - Zahirović, Abida; Zupančič, Špela; Verdir, Andraž; Nemec, Sebastjan; Kralj, Slavko; Snoj, Luka; Berlec, Aleš (Frontiers in Microbiology, 2025)
IntroductionWith growing evidence of clinical efficacy of probiotics in various diseases, safety concerns have arisen regarding the therapeutic use of live probiotic bacteria, especially in critically ill, immunocompromised, and pediatric populations. Serious probiotic-related adverse effects have been reported in these patients, including bloodstream infection and sepsis. This has led to an increased interest in developing postbiotics (non-viable bacterial products) that may exert beneficial effects on the host without the risks associated with administration of live microorganisms. The aim of this study was to explore postbiotic potential of recombinant Lactococcus lactis bacteria that have been engineered to display interleukin 6 (IL6)-targeting affibody (ZIL6) on their surface and are intended for treatment of inflammatory intestinal diseases.MethodsFive different killing treatments were applied to kill bacteria (heat, ethanol, sonication, UV, and gamma irradiation) and their effect on bacterial viability, morphology and functionality was examined in vitro using a combination of different techniques, including microscopy, flow cytometry, immunoassays and cell-based reporter assay.ResultsThe results showed that ZIL6 affibody displayed on L. lactis via non-covalent anchoring withstood the treatments applied to kill bacteria and remained functional after the loss of microbial viability. The degree of functionality was dependent on the type of treatment. Heat-killed cells retained 50% of the activity of live strain, while most of the activity was preserved after exposure of bacteria to ethanol, sonication, UV and gamma irradiation. The applied treatments varied in killing efficacy, whereby ethanol and heat rendered bacteria non-viable, UV and gamma irradiation yielded non-replicative cells, whereas sonication was ineffective in killing L. lactis. Among non-viable cells, ethanol-killed bacteria exhibited the greatest activity and showed high maximum binding capacity of 200 ng IL6 per mg dry cell weight, possessed strong nanomolar affinity for IL6, and inhibited up to 78% of IL6-induced STAT3 signaling.ConclusionThe study demonstrates that functional non-viable bacterial cells can be derived from the recombinant L. lactis with therapeutic proteins displayed on their surface and provides a good foundations for further studies of their postbiotic potential in adjunctive therapy of inflammatory intestinal diseases.